Вплив ІІІ Всеукраїнських Зборів НРУ на подальший розвиток організації - Малиновський, Валентин Ярославович; Malynovskyi, Valentyn Ya. (Університет Короля Данила, 2019)
У статті розглянуто хід і результати ІІІ Всеукраїнських Зборів НРУ. Проаналізовано два підходи майбутнього розвитку цієї громадсько-політичної організації. За підсумками Зборів очевидну перемогу здобув підхід, запропонований В. Чорноволом, що й визначив майбутній розвиток Руху.

The article deals with the course and results of the Third All-Ukrainian Assembly of the Rukh. Two approaches to the future development of this socio-political organization are analyzed. Following the results of the Assembly, the approach, proposed by V. Chornovil, has obvious victory, which determined the future development of the Rukh.
Influence of the Third All-Ukrainian Assembly of the NRU on further development of the organization
Keywords: ІІІ Всеукраїнські Збори Народного Руху України; В. Чорновіл; І. Драч; М. Горинь; Президент України Л. Кравчук; ДемПУ; УРП; III All-Ukrainian Assembly of the NRU; V. Chornovil; I. Drach; M. Goryn; President of Ukraine L. Kravchuk; DemPU; URP